2006
DOI: 10.1680/geot.2006.56.9.585
|View full text |Cite
|
Sign up to set email alerts
|

On the kinematics of 2D tunnel collapse in undrained clay

Abstract: Citation for published item:ysmnD eF F nd wirD F tF nd foltonD wF hF @PHHTA 9yn the kinemtis of Ph tunnel ollpse in undrined lyF9D q¡ eotehniqueFD ST @WAF ppF SVSESWSF Further information on publisher's website: httpXGGdxFdoiForgGIHFITVHGgeotFPHHTFSTFWFSVS Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(45 citation statements)
references
References 6 publications
3
38
0
Order By: Relevance
“…This mechanism does not incorporate slip surfaces. Osman et al (2006) demonstrated that the upper bound theorem applied to distributed shearing mechanism offered a reasonable assessment for collapse, and also matches the displacement field observed in centrifuge tests of tunnel failure in clay (Mair, 1979). It was also demonstrated that the shape of the surface settlement profile remained the same as the magnitude of settlement increased towards failure.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…This mechanism does not incorporate slip surfaces. Osman et al (2006) demonstrated that the upper bound theorem applied to distributed shearing mechanism offered a reasonable assessment for collapse, and also matches the displacement field observed in centrifuge tests of tunnel failure in clay (Mair, 1979). It was also demonstrated that the shape of the surface settlement profile remained the same as the magnitude of settlement increased towards failure.…”
Section: Introductionsupporting
confidence: 59%
“…The vertical displacements in the deformation mechanism ( Fig. 1) proposed by Osman et al (2006) are taken to follow a Gaussian distribution on each successive horizontal plane at depth z below the surface. The distance to the point of inflexion i z is then expressed by…”
Section: Deformation Mechansimmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 3D face stability analysis, their numerical results were better than the values published by Davis et al ͑1980͒ for great values of C / D where Cϭtunnel cover and Dϭtunnel diameter. A somewhat similar approach has been undertaken previously by Osman et al ͑2006͒ for the 2D stability analysis of circular tunnels in a cohesive soil. However, the velocity field was based on the empirical Gaussian settlement trough near the ground surface instead of the analytical elasticity equations.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several kinematical approaches based on continuous velocity fields in limit analysis theory were proposed. Osman et al [12] developed upper-bound calculations of collapse loads in tunnels using a distributed shear deformation mechanism. They assumed that the soil deforms compatibly following a Gaussian distribution within the boundaries of this deformation mechanism and is rigid outside this mechanism.…”
Section: Introductionmentioning
confidence: 99%